The effects of treatment on lipoprotein subfractions evaluated by polyacrylamide gel electrophoresis in patients with autoimmune hypothyroidism and hyperthyroidism - Minarikova, Zuzana; Gaspar, Ludovit; Kruzliak, Peter; Celecová, Zuzana; Oravec, Stanislav (Lipids in health and disease, 2014)
BACKGROUND: Atherogenic dyslipoproteinemia is one of the most important risk factor for atherosclerotic changes development. Hypothyroidism is one of the most common causes of secondary dyslipidemias which results from reduced LDL clearance and therefore raised levels of LDL and apoB. Association between small dense LDL (sdLDL) presentation and thyroid status has been examinated using polyacrylamide gel electrophoresis for lipoprotein subfractions evaluation. METHODS: 40 patients with diagnosed autoimmune hypothyroidism and 30 patients with autoimmune hyperthyroidism were treated with thyroxine replacement or thyreo-suppressive treatment. In both groups lipid profiles, LDL subractions, apolipoproteins (apoA1, apoB), apoA1/apoB ratio and atherogenic index of plazma (AIP) were examined before treatment and in state of euthyreosis. RESULTS: Thyroxine replacement therapy significantly reduced levels of total cholesterol (TC), LDL, triglycerides (TG) and also decreased levels of sdLDL (8,55±11,671 vs 0,83±1,693mg/dl; p<0,001), apoB and AIP. For estimation of atherogenic lipoprotein profile existence an AIP evaluation seems to be better than apoB measurement because of the more evident relationship with sdLDL (r=0,538; p<0,01). Thyreo-suppressive therapy significantly increased levels of TC, LDL, TG and apoB. The sdLDL was not found in hyperthyroid patients. CONCLUSIONS: Atherogenic lipoprotein profile was present in 52.5% of hypothyroid subjects, which is higher prevalence than in normal, age-related population. Substitution treatment leads to an improvement of the lipid levels, TG, apoB, AIP and LDL subclasses. It significantly changed the presentation of sdLDL - we noticed shift to large, less atherogenic LDL particles. Significantly positive correlation between sdLDL and TAG; sdLDL and VLDL alerts to hypertriglyceridemia as a major cardiovascular risk factor.
Keywords: thyroxin; lipoproteiny VLDL; Cholesterol, LDL; Aged; thyreostatika; Aged, 80 and over; lidé středního věku; methimazol; senioři; LDL-cholesterol; apolipoprotein A-I; Antithyroid Agents; Methimazole; lidé; Adult; Hyperthyroidism; Middle Aged; Apolipoprotein B-100; dospělí; elektroforéza v polyakrylamidovém gelu; hypertyreóza; Hashimoto Disease; Thyroxine; Female; senioři nad 80 let; Lipoproteins, VLDL; Male; ženské pohlaví; Hashimotova nemoc; Apolipoprotein A-I; apolipoprotein B-100; mužské pohlaví; Humans; Electrophoresis, Polyacrylamide Gel